Development of Skills in Working with Books of Preschool Children as a Social Need - Isroiljanovna, Ismailova Nilufar (Researchparks Publishing, 2023)
This article discusses the role of parents in helping preschoolers understand books, the category of inquisitive children who ask adults to read books, ways of expressing the connection between pictures and words in books, ways of developing listening and understanding skills, the time and duration of communication, methods of formation are analyzed. skills in working with books, taking into account age characteristics.